Instructive problems of medium diﬃculty in math enviroments of Lithuania - Romualdas Kašuba (Lietuvos Matematikos Rinkinys, 2018)
In the paper an attempt to represent some not too easy and in the same time not diﬃcult, accessible, useful and challenging problems used in Lithuanian math events, as well as in training high-scool and University students, is undertaken.